Design of preventive maintenance plan for medical equipment of the Basic Hospital Alberto Correa Cornejo - Quinteros Sarmiento, Darwin Alexander (2025)
This project seeks to propose a preventive maintenance plan taking into account the state of the medical equipment of the Hospital Basic “Alberto Correa Conejo”. For this, a survey of the information of the medical equipment distributed by the different areas of service of the hospital from 3 fronts is carried out; verifying the status of the equipment and its functionality, thus achieving to understand the conditions in which the hospital equipment is located. In addition to the implementation of the Fennigkon algorithm for the prioritization of maintenance based on the importance of the service generating with it a list of activities to be carried out for the preventive maintenance of each equipment as well as an annual schedule of activities taking into account the planning system applied by the Ministry of Health. Additionally, a market study is used in order to provide a budgetary value for the execution of the maintenance plan completely or partially, taking into account the unit costs presented in 32 similar maintenance service contracts available in the Public Contracting Portal. The results of this project show an initiative for the execution of a maintenance plan and the basis of a budget study in the optimization of the operation of the hospital equipment based on preventive maintenance.